Jafarov , Tariel - (:unkn) unknown (My University, 2026)
Tariyel Ilham oglu Jafarov graduated from the Azerbaijan University of Architecture and Construction (AzUAC) with a Bachelor’s degree in Urban Cadastre in 2007 and a Master’s degree with honors in the same specialization in 2010. He began his academic career in 2011 as a Lecturer at the Department of Geomatics at AzUAC and has served as a Senior Lecturer since 2013. He is currently pursuing a PhD. Tariyel Jafarov is the author of 32 scientific publications, 2 course programmes, and 4 methodological manuals. His research interests include modern geodetic measurement technologies, Geographic Information Systems (GIS), and Remote Sensing in environmental studies. His current research focuses on the monitoring and ecological assessment of forest soils in the Guba and Khachmaz regions using digital mapping and spatial analysis technologies.